ANALISIS PERUBAHAN PEMANFAATAN LAHAN BERDASARKAN MODEL SPASIAL HARGA LAHAN DI KECAMATAN BANDAR KEDUNG MULYO KABUPATEN JOMBANG - Risa Amalia Kurniawati Kurniawati (Journal of Demography, Ethnography and Social Transformation, 2022)
Abstract The construction of the Jombang toll road gate in Bandar Kedung Mulyo District has caused land prices to increase and land-use changes have occurred. Determination of land-use change using 3 spatial models of land prices, namely. (1) Delphi analysis to identify what factors determine land prices, (2) Spatial regression analysis methods for spatial models of land prices, and (3) Query Builder analysis method for map results of land-use change in Bandar Kedung Mulyo District. There are 12 aspects determine land prices from the results of the Delphi analysis. Aspects that have a positive influence on the model are the design of the route network, trade and service facilities, and universal transportation roads. Aspects that have a negative influence are religious facilities, learning facilities, health facilities, office facilities, rivers, collector lanes, industrial estate plans, residential areas, residential area plans, as well as toll gate interchange. The spatial model shows that large land prices are near the toll gate interchange and low land prices are in the border area of ​​Bandar Kedung Mulyo District. Keywords: Jombang toll gate interchange, potential land-use change, land price